Daya Tarik Visual dan Emosional Produk Pop Mart dalam Memengaruhi Perilaku Konsumen: The Visual and Emotional Appeal of Pop Mart Products in Influencing Consumer Behavior - Tanjaya, Tiffany; Yanti, Ni Kadek Winda (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to examine the influence of hedonic motivation, visual appeal, and emotional appeal on purchase decisions for Pop Mart products, as well as to test the moderating role of influencers. A quantitative approach was employed using a survey of 200 Pop Mart consumers in Bali, and the data were analyzed using Partial Least Square (PLS). The findings indicate that hedonic motivation, visual appeal, and emotional appeal each have a positive and significant effect on purchase decisions. Hedonic motivation emerges as a dominant factor, driven by enjoyment, novelty, and emotional gratification. Visual appeal also contributes strongly, particularly through attractive colors and distinctive design elements. Emotional appeal further enhances purchase decisions by creating emotional connections, surprise elements, and personal experiences. However, influencers do not moderate the relationship between hedonic motivation or emotional appeal and purchase decisions, and the moderating effects were found to be insignificant. These results suggest that Pop Mart purchase decisions are shaped more by personal experiences and product aesthetics than by external promotional influences. Overall, the study highlights the crucial role of psychological and aesthetic factors in shaping consumer purchase decisions for collectible toy products such as Pop Mart.